2008
DOI: 10.1124/dmd.108.024943
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Antiviral Prodrug Oseltamivir Is Impaired by Two Newly Identified Carboxylesterase 1 Variants

Abstract: ABSTRACT:Oseltamivir phosphate is an ethyl ester prodrug widely used in the treatment and prevention of both Influenzavirus A and B infections. The conversion of oseltamivir to its active metabolite oseltamivir carboxylate is dependent on ester hydrolysis mediated by carboxylesterase 1 (CES1). We recently identified two functional CES1 variants p.Gly143Glu and p.Asp260fs in a research subject who displayed significant impairment in his ability to metabolize the selective CES1 substrate, methylphenidate. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 20 publications
3
62
0
1
Order By: Relevance
“…Oseltamivir phosphate is rapidly absorbed and converted to oseltamivir carboxylate by CES1 (He et al, 1999). The exception to this rapid conversion is in rare individuals who are poor converters (Zhu and Markowitz 2009). Rare genetic variants have been documented that result in low carboxylesterase activity, and this has led to concerns that individuals with variant alleles will not achieve therapeutic effects because of their inability to hydrolyze the prodrug to its active form.…”
Section: Discussionmentioning
confidence: 99%
“…Oseltamivir phosphate is rapidly absorbed and converted to oseltamivir carboxylate by CES1 (He et al, 1999). The exception to this rapid conversion is in rare individuals who are poor converters (Zhu and Markowitz 2009). Rare genetic variants have been documented that result in low carboxylesterase activity, and this has led to concerns that individuals with variant alleles will not achieve therapeutic effects because of their inability to hydrolyze the prodrug to its active form.…”
Section: Discussionmentioning
confidence: 99%
“…The Flp-In-293 cell lines stably expressing wild-type CES1 and its variants G143E and D260fs have been developed previously and applied to our ensuing CES1 pharmacogenetic studies (Zhu et al, 2008;Zhu et al, 2009b;Zhu and Markowitz, 2009). The minor allele frequency (MAF) of G143E is estimated to be 3.7%, 4.3%, 2.0%, and 0% in Caucasian, Black, Hispanic, and Asian populations, respectively, whereas D260fs appears to be a rare mutation in all racial and ethnic groups studied to date (Zhu et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This variability is likely to be the result of both genetic and environmental factors (Hosokawa et al, 1995;Fukami et al, 2008;Yoshimura et al, 2008;Yang et al, 2009;Zhu et al, 2009a;Shi et al, 2011;Ross et al, 2012). We have reported that the CES1 single-nucleotide polymorphisms (SNPs) G143E (rs71647871) and D260fs (rs71647872) exhibit markedly decreased enzymatic activity toward the hydrolysis of the CES1 substrates methylphenidate, oseltamivir, and trandolapril (Zhu et al, 2008;Zhu et al, 2009b;Zhu and Markowitz, 2009). Furthermore, we and others have demonstrated that some therapeutic agents can significantly inhibit CES1 activity Zhu et al, 2010;Rhoades et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[2,6,7] In-vitro functional studies have demonstrated that the G143E and the D260fs variants have reduced catalytic function, resulting in the disruption of hydrolytic activity of CES1. [8,9] In a single-dose pharmacokinetic study, these two CES1 mutations were identified in one subject who displayed 7-fold higher total methylphenidate (i.e., combined d-and l-isomers) concentrations compared to that of other subjects (n=19). [2,9] In addition, -75T>G polymorphism was associated with the reduced appetite in attention deficit-hyperactivity disorder (ADHD) youths treated with methylphenidate [10] and the isoniazid-induced hepatotoxicity in latent tuberculosis infection patients.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] In a single-dose pharmacokinetic study, these two CES1 mutations were identified in one subject who displayed 7-fold higher total methylphenidate (i.e., combined d-and l-isomers) concentrations compared to that of other subjects (n=19). [2,9] In addition, -75T>G polymorphism was associated with the reduced appetite in attention deficit-hyperactivity disorder (ADHD) youths treated with methylphenidate [10] and the isoniazid-induced hepatotoxicity in latent tuberculosis infection patients. [11] Taken together, these findings suggest that CES1 gene variants can lead to clinically significant alterations in…”
Section: Introductionmentioning
confidence: 99%